2022
DOI: 10.3390/d14030228
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genomic Analysis of G2-like Transcription Factor Genes and Their Role in Development and Abiotic Stresses in Arabidopsis

Abstract: GOLDEN2-LIKE (GLK) transcription factors are a subfamily of GARP family transcription factors, which play an essential function in plant growth and development as well as stress response during abiotic and biotic stress conditions. This study reports GLK genes in the Arabidopsis thaliana genome in-depth and identified 55 AtGLK genes in the Arabidopsis genome. Phylogenetic analyses resolved these GLK gene clusters into seven groups. A Ka/Ks ratios analysis indicated that they had experienced purifying selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 51 publications
4
11
0
Order By: Relevance
“…The synteny relationships of GLK genes between E. grandis and other species showed that the number of homologous gene pairs between E. grandis and dicotyledons was much more than that between E. grandis and monocotyledons, indicating that GLK gene family has been amplified after differentiation between dicotyledon and monocotyledon ( Figure 2 ). The EgrGLK genes were classified into seven groups based on a phylogenetic analysis ( Figure 3 ), which was consistent with the classification of GLK genes in Arabidopsis ( Alam et al, 2022 ). This result indicated that, although some EgrGLK genes were lost during evolution, the sufficient genetic diversity has been retained in E. grandis .…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The synteny relationships of GLK genes between E. grandis and other species showed that the number of homologous gene pairs between E. grandis and dicotyledons was much more than that between E. grandis and monocotyledons, indicating that GLK gene family has been amplified after differentiation between dicotyledon and monocotyledon ( Figure 2 ). The EgrGLK genes were classified into seven groups based on a phylogenetic analysis ( Figure 3 ), which was consistent with the classification of GLK genes in Arabidopsis ( Alam et al, 2022 ). This result indicated that, although some EgrGLK genes were lost during evolution, the sufficient genetic diversity has been retained in E. grandis .…”
Section: Discussionsupporting
confidence: 76%
“…In this study, 40 EgrGLK genes were identified in the E. grandis genome (Supplementary Table S2). The number of EgrGLK genes was less than the number of GLK genes identified in Arabidopsis (55), maize (59), and tomato (66) (Liu et al, 2016;Alam et al, 2022;Wang et al, 2022). It was suspected that some EgrGLK genes were lost during evolution (Du et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Salinity stress is one of the major abiotic stresses limiting plant growth and productivity, it also suppresses the growth of S. polyrhiza [ 60 ]. There are many reports of the GARP genes that responded to salt stress, such as AtGLK2/5/8/20/23/26/34/43/46 in A. thaliana [ 11 ], ZeGLK3 in Z. mays [ 43 ], 27 SiGLK genes in S. lycopersicum [ 61 ], and GhGLK55/120 in G. hirsutum [ 40 ]. In our study, we found that the expression of SpGLK25 was downregulated under salt stress, which helps to explain why the salt stress affects N/P uptake, and growth rate in plants [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…GLK TFs play important roles in biotic and abiotic stresses, such as pathogen infection, salt stress, drought, and nutrient deficiency. AtGLK1 regulates genes that involved in disease resistance and effect on different pathogen [ 10 ], nine AtGLK genes were responded to salt stress in A. thaliana [ 11 ]. Both of Phosphorus Starvation Response 1 (Psr1) in C. reinhardtii and Phosphate Starvation Response 1 (PHR1) in A. thaliana play the central regulatory roles in inorganic phosphate (Pi) sensing system [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%